PENGGUNAAN VARIABEL MEDIATOR DALAM EKSPERIMEN: CONTOH KASUS INTERVENSI PENGATASAN DEPRESI PADA REMAJA - Widhiarso, Wahyu; Retnowati, Sofia (Faculty of Psychology, Diponegoro University, 2012)
The use of a mediator variable which mediates the effect of treatment with the output variable in the context of experimental research is highly recommended. By involving the mediator variable, the mechanism of treatment effect given to the output variable can be explained in more detail. This study aimed to disseminate the use of a mediator variable in experimental research which is rare used among researchers in Indonesia. Two mediation analysis procedures was applied to analyze the effect of Depression Prevention Training to reduced depression symptoms among adolescents. This study employed pretest–posttest experimental design. Participants were divided into two groups and the treatment was given to the treatment groups. The variable defined as mediator was coping skill. Firstly, Baron-Kenny procedure was employed and then followed by causal analysis procedure. The analysis revealed that coping skill was proved as a mediator between the effect of treatment on depression. Similarity and differences of these two procedures were discussed.Keywords : Mediator, Baron-Kenny Procedure, Causal Analysis Procedure